Determinants of community-based home care service demand among urban older adults in Shanxi, China: a cross-sectional psychological perspective - Li, Haoran; Sun, Sijie; Bartomeu-Magaña, Elena; Wei, Xin (Frontiers in Public Health, 2025)
IntroductionGiven China’s large population and the severity of its aging issue, community-based home care has become the primary approach to addressing older adults’ care needs.MethodsThis study combined follow-up visits and questionnaire surveys, using univariate analysis of variance (ANOVA) and multivariate logistic regression to examine the demand for community-based home care services among urban community older adults in Shanxi Province, China.ResultsLogistic regression results identified several significant influencing factors: monthly income, occupation, living conditions, community neighborhood relationships, and community mutual assistance.DiscussionThis study clarifies the characteristics of demand for community aged care services among urban older adults in Shanxi, providing important reference for optimizing such services.